The Discourse Semantics of Attitudinal Relations: Continuing the Study of Lexis - Martin, J R (Vestnik Rossijskogo universiteta družby narodov. Seriâ Lingvistika, 2017)
This paper explores some aspects of the problem of categorizing attitudinal relations in English, as part of a description of evaluation informed by systemic functional linguistics (SFL) - appraisal. It reviews paradigmatic and syntagmatic orientations to lexis within this tradition, and the development of typological and topological representations of systemic relations. Corpus based argumentation is considered in relation to work on evaluation by Bednarek 2008; and proposals for continuing the study of lexis are suggested, focusing on resources for negotiating sadness and negative reactions to behavior (e.g. embarrassed , ashamed ) and the affordances of topological representation. The paper highlights the possibilities and challenges involved in continuing the study of lexis in descriptions using SFL as their informing theory.